Conceptual framework for factors affecting construction quality in Johor, Malaysia - Woo, Yu Ting; Abas, Nor Haslinda; Mohd Ali, Noor Helmie Shahreen (2024)
Maintaining high construction quality is a constant challenge as quality problems affect building safety, increase maintenance costs, and reduce user satisfaction. This study investigates the factors influencing construction quality in Malaysia, with a particular focus on Johor, in the context of rapid urbanisation and growing infrastructure demands. A total of 33 factors were extracted and categorised from the literature and organised into a questionnaire with 12 major groups. This survey was completed by 125 construction professionals who returned their responses. Cronbach Alpha was used to examine the reliability of the collected data before proceeding to the Relative Importance Index (RII) in determining the relative ranks of identified factors. Based on the analysis, it is identified that the most significant factors are lack of expertise, followed by inconsistent design documents, insufficient cooperation between contractors, resource availability, weather conditions, and management skills. The findings offer practical recommendations for authorities and stakeholders to improve building quality. They provide an overview of high and low ranks of factors and raise awareness of quality issues that must be addressed.